Pengaruh Parent-Child Relationship terhadap Compulsive Buying: Self-Esteem sebagai Variabel Mediasi - Lu, Cen; Suwarno, Henky Lisan (Zenit, 2015)
Consumer behavior, especially consumer purchases have been subject to change in tha past few years. Consumer purchase includes some types of purchase, and it is an interesting issue to study. Compulsive buying encourages consumers to make purchases in large and excessive amounts thoughnot really necessary. Compulsive buying is influenced by parent-child relationship in which the relationship of parents and children in the family influences consumer purchase decisions from the negative impact of the existing purchasing decisions. Parent-child relationship consists of three dimensions, namely parent-child cohesion, parent-child expressiveness, and parent-child conflict. Parent-child relationship can lead consumers to materialistic orientation. Consumers with Parentchild cohesion have excessive psychological pressure when shopping. Parent-child expressiveness gives freedom to the family members to make an expression when making purchases. Parent-child conflict shapes a consumer anti-social and deviant behavior in their purchasing behavior. Theinfluence of parent-child relationship towards compulsive buying is mediated by self-esteem. Selfesteem gives low self-esteem that makes consumers vulnerable to the purchase of deviant behavior. Compulsive buying is excessively a repetitive purchasing behavior and has become a habit forconsumers. This type of research is explanatory research. The results show that parent-child relationship does not affect compulsive buying simultaneously, whereas the partial test results has found out that parent-child cohesion and expressiveness do not affect compulsive buying, whileparent-child conflict does. Self-esteem, on the other hand, does not mediate the effect of parent-child relationship towards compulsive buying.Keywords: Parent-child relationship, Compulsive buying, self-esteem